Comparison of CO-RADS, RT-PCR and Chest CT Score; a report of 519 cases (Annals of Medical Research, 2023)
Aim: Analysing the efficancy of The Dutch COVID-19 Reporting and Data System (CO-RADS) classification to evaluate the severity of the disease of patients with COVID-19 infection and investigating its diagnostic performance with the correlation between reverse transcriptase-polymerase chain reaction (RT-PCR) test results and severity of the disease.Materials and Methods: Retrospective evaluation of the RT-PCR and the Computed Tomography (CT) imaging results of 519 patients who were clinically accepted and threated as Covid-19.  Inclusion criteria: All patients over the age of 18 who underwent CT with a pre-diagnosis of covid were included. The study excluded patients who were under the age of 18, pregnant, in poor general health but unable to undergo a CT scan, whose data could not be retrieved, or whose data were input insufficiently. Three radiologists evaluated the Chest CT images by using the CO-RADS and the CT Score classifications. Relationship between CORADS, Chest CT Score and RT-PCR results were demonstrated.  Demographic data, clinical features, comorbidities, hospitalization rates and intensive care unit admission were recorded and correlated with CORADS and CT Score classification.Results: The average age was 46.41± 17.37 (range 18-95). 232 cases were women, while 287 cases were men. 278 (53.5 %) of 519 patients had positive RT-PCR results. According to kappa results; there is no agreement between CORADS and RT-PCR, CORADS and CT Score. 278 (53,6 %) of 519 patients had positive RT-PCR results. According to kappa results; there is no agreement between CO-RADS and RT-PCR, CORADS and CT Score. There was correlation between CT score and man population (p
Keywords: COVID-19; Computed tomograpy CORADS; Polymerase chain reaction